ANALISIS SELF REGULATED LEARNING MAHASISWA PAI IAIN BATUSANGKAR (STUDI MAHASISWA PAI SEMESTER III ANGKATAN 2017) - Pebrina, Rizki; Putri, Ica Yuliana (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The main problem in this study is related to student learning styles that are still not optimal, and tend to be teacher centered, and lack of preparation in learning. The purpose of this study is to describe the Self Regulated Learning of PAI IAIN Batusangkar Students in metacognitive aspects, motivation and active behavior. The type of research used is the type of field research (Field Research) with quantitative descriptive methods. Data collection techniques using a questionnaire. The data analysis technique that the author uses in this study is quantitative analysis that is descriptive statistics used to analyze data by describing or describing the data collected. Then present it in the form of a diagram. From the research that has been done, it is obtained that the overall picture of Self Regulated Learning of PAI 2017 Batusangkar IAI Class is classified as high with a percentage of 71.77%. The picture of Self Regulated Learning based on metacognitive aspects obtained a percentage of 67.65% with the category